Peran Kepemimpinan dalam Menciptakan Kerjasama Tim pada Perusahaan - Kusumawati, Nia (Amsir Management Journal, 2024)
This study examines the impact of leadership on fostering effective teamwork within an organization. Utilizing a literature review methodology, this research analyzes, identifies, and evaluates various articles and journals to present comprehensive findings. The results indicate that leadership plays a pivotal and influential role in team dynamics. Given that leadership styles vary, it is imperative for leaders to adeptly manage and guide their team members towards the attainment of the organization's objectives. An exemplary leader is one who can inspire team members to unite under a shared vision for target achievement. Enhanced teamwork and cohesion are likely when guided by supportive and directive leadership. This study aims to underscore the significance of leadership in bolstering teamwork to realize organizational goals, thereby advocating for the establishment of a robust leadership system across businesses.